(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This research with a quantitative-qualitative model, action research design and correlational scope, aims to address two problems of bilingual education. First, the need to apply a communicative approach to vulnerable populations and those with special educational needs. The second is the deficiency in the oral production component expressed in low levels of oral fluency. The objective of this research is to carry out a didactic intervention based on Task-Based Learning (TBL) and to impact oral fluency in students belonging to vulnerable populations and with special educational needs at the Centro de Prácticas Educativas y Sociales of the Universiy of Quindío. The research is based on ABT from Willis’ perspective and oral fluency from authors such as Lennon. The research was divided into cycles of diagnosis by means of an entrance test, intervention, and evaluation by means of an exit test. Finally, data were collected through a field diary and interviews which showed that 50% of the students involved went from having limited levels to "adequate" or "strong" levels in L2.